PENGGUNAAN METODE DISKUSI KELOMPOK DAN PEMBERIAN TUGAS DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR EKONOMI MATERI PERTUMBUHAN EKONOMI SISWA KELAS XI IPS 4 SMA NEGERI 1 PUNGGUR SEMESTER GANJIL TAHUN PELAJARAN 2015/2016. - Purwati, Purwati (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
To get good result in learning process, teacher should be able to improve herself  by using many kinds of methods so that the result can be improved and students can be active in teaching learning process. The purpose of this research is to know whether the use of discussion and giving task can improve learning achievement in a material of economic growth at the class of XI IPS 4 SMAN 1 Punggur year 2015/2016. To get good result in learning process teacher should be able to improve herself  by using many kinds of methods so the result can be improved and students can be active in teaching learning process. The purpose of this research is to know whether the use of discussion and giving task can improve learning achievement in a material of economic growth at the class of XI IPS 4 SMAN 1 Punggur year 2015/2016. The location of this research is in SMAN 1 Punggur. It is done for 3 months , August to October 2015. Subject of this research is Class XI IPS 4 of  SMAN 1 Punggur in the academic year of 2015/ 2016.  Technique of collecting data used are : observation, documentation and data analysis interview by using qualitative descriptive analysis. Research procedure uses classroom action research method that consists of 2 cycles. The result of the classroom action research shows that In pre cycle, students who pass / succeed are 10 from 31 students or 32.14% and fail students are 21 from 31 students or equal to 6.86 %. After getting treatment in the first cycle, passed students increases to 22 from 31 students or 75% while fail students decrease 10 from 31 students or 25%. In the second cycle, passed students increases to 29 from 31 students or 92.86% while failed students only 2 from 31 students. Based on the data above it can be concluded that by using discussion method and giving task can improve thestudents’ economy achievement with economic growth material at the XIGrade of Social Science 4 in SMAN 1 Punggur on odd semester in the academic year of 2015/2016is true. Keywords : Discussion method and giving task, Learning achievement.